2004
DOI: 10.1172/jci200420480
|View full text |Cite
|
Sign up to set email alerts
|

Defining the pathogenic involvement of desmoglein 4 in pemphigus and staphylococcal scalded skin syndrome

Abstract: Desmogleins (Dsgs), cadherin-type cell adhesion molecules, are targeted in skin-blistering diseases such as pemphigus and staphylococcal scalded skin syndrome (SSSS). The role of Dsg4, a new isoform, was investigated in these diseases. Dsg4 was recognized by 30 (77%) of 39 pemphigus sera containing anti-Dsg1 IgG but not by 16 pemphigus sera containing no anti-Dsg1 IgG or by 34 normal control sera. The Dsg4 immunoreactivity of these sera was abolished by removal of anti-Dsg1 IgG. Conversely, the removal of anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 36 publications
0
24
0
1
Order By: Relevance
“…Recombinant, secreted-form extracellular domains of mouse Dsg1a, Dsg1b, Dsg1g, and Dsg4, fused with E-and His-tags on their carboxyl terminus, were produced using the baculovirus expression system as described previously [13][14][15]. Culture supernatants of High Five TM insect cells (Invitrogen Corp., Carlsbad, CA) containing recombinant mouse Dsg were collected and stored at À70 8C after removal of cell debris by centrifugation.…”
Section: Production Of Recombinant Mouse Dsgmentioning
confidence: 99%
“…Recombinant, secreted-form extracellular domains of mouse Dsg1a, Dsg1b, Dsg1g, and Dsg4, fused with E-and His-tags on their carboxyl terminus, were produced using the baculovirus expression system as described previously [13][14][15]. Culture supernatants of High Five TM insect cells (Invitrogen Corp., Carlsbad, CA) containing recombinant mouse Dsg were collected and stored at À70 8C after removal of cell debris by centrifugation.…”
Section: Production Of Recombinant Mouse Dsgmentioning
confidence: 99%
“…Dsg3 is the autoantigen in mucocutaneous-type PV and mucosal dominant-type PV (Amagai et al, 1991(Amagai et al, , 1994Koch et al, 1997;Mahoney et al, 1999). Pemphigus sera occasionally contain Dsg4/Dsg1 cross-reacting IgG autoantibodies (Kljuic et al, 2003;Whittock and Bower, 2003;Nagasaka et al, 2004). No reactivity against Dsg2 was found in PF or PV sera (Ota et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…The antigen recognized by the autoantibodies in patients with Pemphigus vulgaris was cloned by Amagai et al showed that the Pemphigus vulgaris antigen is desmoglein 3(Dsg3) and serum from patients with pemphigus foliaceus contains antibodies that bind to desmoglein 1(Dsg1), members of the desmoglein family (Amagai et al, 1991). The pathogenic role of autoantibodies against Dsg1 and Dsg3 has been clearly established, despite the identification of potential additional autoantigens such as α-9-acetylcholine receptor , pemphaxin , and, recently, Dsg4 (Kljuic et al, 2003;Nagasaka et al, 2004).…”
Section: Introductionmentioning
confidence: 99%